2019
DOI: 10.1080/13647830.2019.1602286
|View full text |Cite
|
Sign up to set email alerts
|

Experimental data-based reduced-order model for analysis and prediction of flame transition in gas turbine combustors

Abstract: In lean premixed combustors, flame stabilization is an important operational concern that can affect efficiency, robustness and pollutant formation. The focus of this paper is on flame lift-off and re-attachment to the nozzle of a swirl combustor. Using time-resolved experimental measurements, a data-driven approach known as cluster-based reduced order modeling (CROM) is employed to 1) isolate key flow patterns and their sequence during the flame transitions, and 2) formulate a forecasting model to predict the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Specifically, this work employs a maximumoverlap discrete packet wavelet transform (MODPWT) in the MRPOD to isolate PVC from low-frequency dynamics (LFD), such that their influences on the flow field as well as on soot volume fraction (f v ) can be separately evaluated. Beside POD-based methods the cluster-based reduced-order modeling (CROM) method [8,9] with its probabilistic nature, may also prove appropriate at treating the nonlinear LFD. mary injector consists of two concentric, swirled airflows, into which ethylene is injected co-axially via 64 rectangular channels.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, this work employs a maximumoverlap discrete packet wavelet transform (MODPWT) in the MRPOD to isolate PVC from low-frequency dynamics (LFD), such that their influences on the flow field as well as on soot volume fraction (f v ) can be separately evaluated. Beside POD-based methods the cluster-based reduced-order modeling (CROM) method [8,9] with its probabilistic nature, may also prove appropriate at treating the nonlinear LFD. mary injector consists of two concentric, swirled airflows, into which ethylene is injected co-axially via 64 rectangular channels.…”
Section: Introductionmentioning
confidence: 99%
“…The clustering process is done in an unsupervised manner using K-means clustering [46][47][48], which has been successfully applied in a variety of fluid applications [49][50][51][52]. The K-means algorithm takes as an input a number of clusters and subsequently groups the realizations (or snapshots) into these many clusters.…”
Section: K-means Clusteringmentioning
confidence: 99%
“…In the following results, the distance chosen for the clustering is the L 2 norm computed in physical space. While this choice has been sufficient in other applications [49][50][51], it is not necessarily ideal. Other distance measures based on image recognition concepts were investigated [58], though these led to the same conclusions as the ones presented in Sec.…”
Section: The Number Of Clusters and The Normmentioning
confidence: 99%
“…Majority of the efforts has been spent in characterizing the combustor pressure signal and detecting temporal precursors by various reduced order modeling, time series analysis (Gotoda et al (2011); Murayama et al ( 2018)), and signal processing (Nair and Sujith (2014); Sen et al (2018Sen et al ( , 2016; Barwey et al (2019a)) or machine learning approaches (Sarkar et al (2015b)).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%
“…The common methods for coherent structure detection are rotational symmetry(Ramanan and Chakravarthy (2019)), proper orthogonal decomposition (POD)(Berkooz et al (1993); LoCurto et al (2018)) (similar to principal component analysis(Bishop (2006))) and dynamic mode decomposition (DMD)(Schmid (2010);Ghosal et al (2016)), which utilize spectral theory to derive spatial coherent structure modes. Although these methods have widespread applications in understanding spatiotemporal flow characteristics, it is shown that they demonstrate high parametric sensitivity for instability detection purposes and their applicability does not extend to noisy line-of-sight videos at par with more realistic data collection scenario.Using artificial neural networks and clustering methods, studies(Barwey et al (2019a(Barwey et al ( ,b, 2020;Cui et al (2020)) have been performed in the domain of combustion systems, especially on fluid mechanical aspects of combustion and identifying mapping between flow-field and heat release rate markers. Researchers have also shown early instability detection capability by combining complex networks and machine learning(Kobayashi et al (2019)) and have used Bayesian machine learning for combustion diagnostics(Sengupta et al (2020)).…”
mentioning
confidence: 99%